2011
DOI: 10.1007/s10926-011-9304-6
|View full text |Cite
|
Sign up to set email alerts
|

What Facilitates Return to Work? Patients Experiences 3 Years After Occupational Rehabilitation

Abstract: Objective We have limited knowledge about the specific elements in an occupational rehabilitation programme that facilitate the process leading to return to work (RTW) as perceived by the patients. The aim of the study was to explore individual experiences regarding contributing factors to a successful RTW, 3 years after a resident occupational rehabilitation programme. Methods The study is based on interviews of 20 individuals who attended an occupational rehabilitation programme 3 years earlier. Ten informan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
93
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 39 publications
(35 reference statements)
10
93
0
1
Order By: Relevance
“…This cause of sick leave may be improved if work-related interventions are addressed to the problems causing the sick-leave spell. We also found that rehabilitation support from the workplace, including support from the employer, workmates and other stakeholders, which is found to be important in the process of returning to work (20,21), was given to a higher degree for patients with MD compared with patients with MSD.…”
Section: Work-related Interventionsmentioning
confidence: 79%
See 3 more Smart Citations
“…This cause of sick leave may be improved if work-related interventions are addressed to the problems causing the sick-leave spell. We also found that rehabilitation support from the workplace, including support from the employer, workmates and other stakeholders, which is found to be important in the process of returning to work (20,21), was given to a higher degree for patients with MD compared with patients with MSD.…”
Section: Work-related Interventionsmentioning
confidence: 79%
“…The importance of providing work-related interventions and adaptation of work for sick-listed From a patient perspective, it appears that support and adjustment at the workplace is a facilitating prerequisite for RTW (19)(20)(21), and specific goals for each patient can benefit the RTW process (18,30,32). We found that adjustments to work tasks or the work environment were the most prevalent interventions at the workplace for both diagnostic groups.…”
Section: Work-related Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social support can facilitate sick listed peoples' return‐to‐work processes 10, 11. However, different actions from different sources can be perceived as more or less supportive considering the circumstances 12.…”
Section: Introductionmentioning
confidence: 99%